Pengaruh Digital Marketing, Self Service Technology, dan Kualitas Pelayanan terhadap Kepuasan Nasabah Bank Mega Syariah Cabang Malang - Gebbril Oktavia Jaya; Budi Wahono; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study is to determine and analyze the influence of digital marketing, self service technology, and service quality on customer satisfaction of Bank Mega Syariah Malang City. In this study there are 3 independent variables to measure customer satisfaction, namely digital marketing, self service technology, and service quality. The population in this study is all customers of Bank Mega Syariah Malang City, and the sample in this study uses the slovin formula, so that a sample of 100 respondents was obtained. The data used in this study is primary data, the data collection method is carried out by distributing questionnaires that have been made using google forms. The data analysis techniques used are descriptive statistical analysis, validity and reliability tests, classical assumption tests, and multiple regression. The results of this study show that digital marketing has a significant effect on customer satisfaction, self service technology has a significant effect on customer satisfaction, service quality has a significant effect on customer satisfaction Bank Mega Syariah Malang City. Keywords: Digital Marketing, Self Service Technology, Kualitas Pelayanan, Kepuasan Nasabah